Pluralita identit v kultuře afroamerického ghetta - Procházková, Eva (Lidé města, 2017)
Identity research is the subject of many scientific disciplines. In the most general terms, identity can be perceived as a certain ability to become aware of and to define one’s self. The main objective of the paper is a comprehensive overview of a theoretical study addressing the diverse identities that arise, form, and overlap in the specific environment of the African-American ghetto. It is based on the findings of significant ethnographic studies, fieldwork, autobiographies, interviews, and other sources that deal with the subject. In the introduction, I will focus on the etymology of the concept, history, and well-known theories defining ghetto culture. The main focus will be on the different perceptions of territorial belonging and the formation of ethnic identity throughout history. On the basis of selected literary sources, I will present some individual and group identities that have been formed in the environment in relation to lifestyle, to ways of livelihood, and to local subcultures. In the conclusion, I will highlight some contemporary ghetto issues, such as the consequences of globalization, gentrification and touristification.